Le foisonnement éolien : les limites d’un mix électrique à forte proportion d’énergies renouvelables intermittentes - Grand, Dominique; Fontecave, Marc (Comptes Rendus. Chimie)
Intermittency of wind and solar productions raises the concern of finding other sources of electricity to match the consumption when an hibernal anticyclone reduces dramatically wind production. In this situation occurring every year the stress on the grid is at maximum with the consumption at a peak and a low photovoltaic production. Despite these risks, scenarios still aim at high shares of wind and solar in the electricity mix of 2050, assuming that different wind regimes in Europe would allow France to import wind productions from its neighbors when in need.The study considers a typical situation given by hourly wind productions of the first two months of 2020, in France and in the closest countries. Assuming a full renewable electricity mix officially envisioned in France and Germany for 2050, the exchanges are computed and illustrated for the two months, with a focus on an anticyclone which occurred in the second part of January. The exchanges will not solve the shortage in France and it could even worsen it. The 50–50 renewable and nuclear scenario is given for comparison, showing that the solution lies in providing adequate secured power plant capacity.